Influence of agro-meteo-conditions on main economically valuable parameters in long-fibred flax - N. S. Koshcheeva; I. V. Lyskova; S. N. Kraeva (Аграрная наука Евро-Северо-Востока, 2016)
Results of studying influence of agrometeoconditions on the basic economically valuable parameters (productivity, content of fibre and its quality) of long-fibred flax in the east of the central agroclimatic zone of the Kirov region during 2001 ... 2015 are stated in the article. For last 15 years, a tendency is observed of increase of a temperature mode and decrease in an amount of precipitation in May, i.e. during the period «sowing - seedling» that extended approach of a phase "seedlings". The period of fast growth of long-fibred flax's plants in the conditions of Falenki Plant-Breeding Station fall at June. Productivity of straw and fiber in long-fibred flax is considerably reduced with short-term droughts if they coincided with this period. The lack of moisture in June has been noted in 33.3% of years of researches. Essential correlations of productivity parameters of varietal collection of long-fibred flax with hydrothermal factor of June are established. The technical height of plants depended on agro-meteorological conditions in period of fast growth (r = 0.81), productivity of straw and accordingly productivity of a fibre (r = 0.71), and duration of the growing season (r = 0.54). The sums of effective temperatures have render negative influence on the content of fibre and its quality (flexibility and durability) (r = -0.15; -0.60; -0.36 accordingly). Optimum conditions of development of economically valuable parameters of long-fibred flax on the sum of effective temperatures and a GTK have developed in 2009 - the sum of effective temperatures for the growing season has made 1205 °С, GTK - 1,49. Samples of domestic breeding were selected by yield of seed, straw, and fibre- Jubilejnyj-87, G-4254, АР4, АР5, АР6 (Research institute of flax);- Pskovskij 93, Antej (Pskov Agricultural Research Institute); TOST 4 (Siberian research institute of agriculture and peat); Dashkovsky 2, Stroitel', Soglasie, Start (Belarus); Rushnichok (Ukraine).